Survival and persistence of foodborne pathogenic and indicator bacteria in spatially separated integrated crop-livestock farms - Goodwyn, Brian; Millner, Patricia; Punchihewage-Don, Anuradha Jeewantha; Schwarz, Melinda; Hashem, Fawzy; Bowers, John; Biswas, Debabrata; Parveen, Salina (Frontiers in Sustainable Food Systems, 2023)
Certified organic production prohibits chemical fertilizer use but permits the application of biological soil amendments of animal origin (BSAAOs) to croplands for fertilizing soil. For fresh produce likely to be consumed uncooked, the United States Department of Agriculture National Organic Program (USDA-NOP) stipulates a 90-day withholding period between BSAAO application and crop harvest for produce not in direct contact with soil to reduce concerns about potential pathogen contamination from BSAAOs. For fresh produce crops in direct contact with soil this withholding period is 120-days. In this study, survival and pathogenesis of three foodborne pathogens and indicator bacteria in BSAAO-amended soils were analyzed with their potential to transfer to produce harvested from three organic, integrated crop-livestock farms (ICLFs) on the Maryland Eastern Shore. In total, 428 manure/compost, soil, untreated produce, and water samples were collected before/after BSAAO incorporation and monthly for 180-days. Samples were assessed for the presence of Listeria monocytogenes (L. monocytogenes), Salmonella, and Shiga toxin-producing E. coli (STEC) with associated virulence factor (VF) genes (STEC/VF-genes), and for aerobic plate count (APC), generic E. coli (gEC), and total coliform levels using standard methods and polymerase chain reaction (PCR). Overall, 18.4% (26/141) of produce samples were positive for at least one tested pathogen, with STEC/VF-genes being detected the most. Produce was contaminated with at least one pathogen and indicators 90- and 120-days post-BSAAO incorporation. Salmonella wasn’t detected in manure/compost samples, and 6.7% (1/15) and 66.7% (10/15) of manure/compost samples were positive for L. monocytogenes and STEC/VF-genes, respectively. In BSAAO-amended soils, 29.1% (74/254) were positive for at least one of the tested pathogens in this study. STEC/VF-genes were detected in 24.0% (61/254) of soils, while L. monocytogenes and Salmonella were detected in 4.3% (11/254) and 0.8% (2/254) of soils, respectively. These three pathogens were detected in soils directly after BSAAO incorporation but were followed by a reduced prevalence. However, pathogens were detected in soils 90- and/or 120-days post-application. The results of this study indicated pathogens associated with BSAAOs (contaminated manures/composts) can persist after soil incorporation and transfer to harvestable produce grown on ICLF’s on the Maryland Eastern Shore. Therefore, further research into withholding periods and other mitigation strategies is necessary to mitigate pathogen contamination risks on ICLFs.